Implementation of Muhadharah Program in PAI Learning in Instilling Student Self-Confidence - Tambunan, Siti Nurhaliza; Mardianto (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
This research aims to determine the presentation of the muhadharah program and the impact of implementing muhadharah in instilling students' self-confidence at Muhammadiyah 48 Medan Private Middle School. Self-confidence is one of the important things in an individual. This is because it is related to how they actualize the abilities, potential, talents and interests that they have since birth or that arise as a person develops in their life. This research uses qualitative research. This research is field research ( Field Research ). This research is included in the type of qualitative descriptive research, which means describing the situation using information that supports it. The data sources that will be used in this research consist of two types of data, namely primary data and secondary data. The techniques used are observation, interviews and documentation. The results of this research show that: (1)This program helps students to develop their potential and find out where their potential lies, whether they are competent in giving speeches, reading the Koran , protocols and recitations. (2) The significant differences that occur in students regarding their level of self-confidence through implementing the muhadarah program can be seen through changes in self-confidence starting from grade 7, 8 and 9.